2020
DOI: 10.1097/opx.0000000000001585
|View full text |Cite
|
Sign up to set email alerts
|

Visual Demand and Acuity Reserve of Chinese versus English Newspapers

Abstract: SIGNIFICANCE This study suggests that Chinese newspaper characters are more legible than English newspaper letters. Characters in Chinese newspapers have higher acuity reserve than English newspapers. PURPOSE The purpose of this study was to evaluate visual demand and acuity reserve for Chinese newspapers in comparison with published data on U.S. newspapers. METHODS The test distances for visual acuity in Chinese clinical studies were reviewe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Charts based on logMAR principles are preferred, be the reduced-size Bailey--Lovie and ETDRS charts or charts containing lower case words that follow a logarithmic progression such as Bailey-Lovie word reading charts [155] or the Minnesota Low-Vision Reading Test (MNRead) [156] (see Section 5.4). Testing of intermediate visual acuity may be conducted at 100, 80 or 66 cm and near visual acuity at 40 or 33 cm, depending on the regulatory standards and practice for a given country [157]. These correspond to vergence ranges from -1.00 D to -3.00 D.…”
Section: Visual Acuitymentioning
confidence: 99%
“…Charts based on logMAR principles are preferred, be the reduced-size Bailey--Lovie and ETDRS charts or charts containing lower case words that follow a logarithmic progression such as Bailey-Lovie word reading charts [155] or the Minnesota Low-Vision Reading Test (MNRead) [156] (see Section 5.4). Testing of intermediate visual acuity may be conducted at 100, 80 or 66 cm and near visual acuity at 40 or 33 cm, depending on the regulatory standards and practice for a given country [157]. These correspond to vergence ranges from -1.00 D to -3.00 D.…”
Section: Visual Acuitymentioning
confidence: 99%
“…Secondly, due to the nature of Chinese characters, which need to be 1.54 times larger than English letters to provide equivalent acuity reserve, individuals tend to be closer to books or newspapers. 8 A study evaluating the impact of viewing distance on normal Chinese reading indicated that 35 cm was the optimal viewing distance. 9 The study revealed that the maximum mean reading rate of 494 characters per minute occurred at approximately 35.0 cm, corresponding to an optimal visual angle (horizontal and vertical) of 0.5 degrees for each character.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, mean preferred reading distances between 32 cm and 41 cm has been reported in patients undergoing cataract surgery implanted with different modalities of multifocal IOL [ 11 14 ]. Furthermore, it has been demonstrated that there are some differences in visual demands and preferences among Asiatic and European individuals, being this another factor to consider [ 18 , 19 ]. Recently, a new device capturing information about daily activities, working visual distances and illumination conditions has been developed (Vivior Monitor system, Vivior AG, Zürich, Switzerland), which can be especially useful for evaluating visual requirements and habits before and after cataract surgery with implantation of PC IOLs.…”
Section: Introductionmentioning
confidence: 99%